Intratympanic steroid therapy in moderate sudden hearing loss: A randomized, triple‐blind, placebo‐controlled trial1. (1st February 2013) - Filipo, Roberto; Attanasio, Giuseppe; Russo, Francesca Y.; Viccaro, Marika; Mancini, Patrizia; Covelli, Edoardo
Abstract: Objectives/Hypothesis: To investigate the efficacy of an intratympanic steroid as a first‐line therapy in patients affected by moderate idiopathic sudden sensorineural hearing loss (ISSNHL). Study Design: Prospective, randomized, triple‐blind, placebo‐controlled trial. Methods: Fifty patients presenting with moderate idiopathic sudden sensorineural hearing loss involving all frequencies from 250 Hz to 8, 000 Hz (a flat audiogram) were enrolled. Patients were randomized into two groups of 25 each. The first group (intratympanic steroid) underwent a daily intratympanic administration of prednisolone for 3 consecutive days. Subjects in the second group (control) received a daily intratympanic injection of a saline solution for 3 consecutive days. Audiometric tests were performed at day 7 after the beginning of therapy (T1), and then 10 and 30 days after T1. The patients in both groups who did not show a complete recovery at T1 were treated with oral prednisone at a tapering dose. Results: In the intratympanic steroid group, 19 out of 25 patients presented at T1 complete recovery (76%), whereas in the control group the number patients who recovered completely at T1 was five out of 25 (20%). The mean pure‐tone average (PTA) recorded at T1 shows a statistically significant improvement in the hearing threshold of the first group compared to the control group ( P < .01). Conclusions: The mean PTA recorded after the first‐line approach (T1) demonstrated a significant therapeutic action of the short‐duration intratympanic steroid therapy on moderate ISSNHL, with a flat audiogram shape, compared to the natural course of the disease and the placebo effect at that time point. Laryngoscope, 2013